Women’s Quarters, an Influential and Political Pole: A Study of the Frankish Inner-Court (Sixth–Seventh Century) - Justine Cudorge (Royal Studies Journal, 2022)
The question of women exercising power and influence appears to be central, if not fundamental, to gender studies, as it allows an in-depth reflection on both societal norms and the way we perceive them today. The historian’s vision has been biased for a long time by a dichotomic consideration of society, with a clear gendered partition where women would have been confined to the private, domestic sphere. Their actions were thus perceived as inconsequential at best, invisible at worst, for they were perpetually limited to private quarters and familial intimacy, while men’s authority and actions supposedly influenced the public sphere and politics in a larger measure. It would be a mistake, however, to keep considering that politics and familial intimacy should be studied separately. The palace environment in particular proves to be especially favorable to women’s authority, for they often benefit from a specific access to the sovereign that even major dignitaries can be deprived of, seeing as they are generally not received privately by the ruling dynasty. Studying women’s quarters thus brings to light a mosaic of interdependent relationships, of intercessors, factional processes, and intricate political networks. Although women can be, and often are, limited in some specific ways, such as their physical presence within the public space, they can still achieve political relevance and play a key role within the palace hierarchy and court mechanics. In other words, women are not only instrumental in displaying royal authority but can, at times, fully embody it without specifically causing a break with tradition. Merovingian private quarters in particular offer a very meaningful example, in that they are a reflection of the Merovingian matrimonial practice—polygyny. By multiplying the female pole within the palatial structure, power and authority come into play, taking various shapes and influencing many areas of the political and private life of the sovereign.